Less is more: the lack of autoinducer-2-dependent quorum sensing promotes competitive fitness of Escherichia coli strain 83972 - Keizers, Marla; Mukherjee, Krishnendu; Berger, Michael; Dobrindt, Ulrich (Frontiers in Cellular and Infection Microbiology, 2025)
Autoinducer-2 is a signaling molecule involved in quorum sensing in Escherichia coli. Quorum sensing enables coordinated behavior based on cell density and helps bacteria adapt to their environment. The luxS gene and the lsr locus are involved in the biosynthesis, transport, and intracellular phosphorylation of autoinducer-2. Disruption of autoinducer-2 biosynthesis or transport can reduce biofilm formation, chemotaxis, and the expression of genes relevant for the uropathogenicity of E. coli. Interestingly, most isolates of E. coli phylogroup B2, in which uropathogenic and other extraintestinal pathogenic strains are overrepresented, lack the lsr operon. We show that autoinducer-2-dependent quorum sensing is not fundamentally beneficial for efficient and prolonged urinary bladder colonization. We demonstrate that the lsr-negative asymptomatic bacteriuria isolate 83972 has a higher fitness than its lsr-complemented variant. Using transcriptome analyses, competitive growth assays, and comparisons of selected fitness properties, we show that restoration of the lsr operon in this strain background results in growth retardation, loss of competitiveness, and higher sensitivity to oxidative stress. Our results illustrate that the lack of autoinducer-2-dependent quorum sensing contributes to the well-known fitness and competitiveness of E. coli 83972, on which its effective use for bacterial interference in the urinary bladder relies. It is vital to delve deeper to fully understand the fitness and competitiveness of the ABU strain 83972 if we are to optimize its use in therapeutic colonization. The key is to unravel the underlying molecular mechanisms, thus ensuring the efficacy and safety of this treatment as an alternative to antibiotic therapy.